Effect of arrow shaft straightness on arrow grouping - Park, J. L.; Aitchison, P. J.; Bielby, A. J.; Bleakley, V.; Carberry, T. P.; Ellis, R. M.; Kerner, R. D.; MacDonald, A. D.; Oosthuizen, D.; Pankhurst, S. B.; Psarakis, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Arrows are available in various straightness grades. Their grouping ability as the straightness varied was assessed using a compound bow and shooting machine. The research showed that archers would benefit from selecting arrows with the highest straightness grades (as might be expected). In addition, nock selection was determined to significantly impact group size. The fletches needed to be set at an angle to the longitudinal axis of the arrow shaft in order to have the arrows spin while in free flight, as that further reduced the group size.